2016
DOI: 10.1186/s12877-016-0245-y
|View full text |Cite
|
Sign up to set email alerts
|

How older adults with mild cognitive impairment relate to technology as part of present and future everyday life: a qualitative study

Abstract: BackgroundExisting everyday technology as well as potential future technology may offer both challenges and possibilities in the everyday occupations of persons with cognitive decline. To meet their wishes and needs, the perspective of the persons themselves is an important starting point in intervention planning involving technology. The aim of this study was to explore how persons with mild cognitive impairment relate to technology as a part of and as potential support in everyday life – both present and fut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
59
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(62 citation statements)
references
References 41 publications
3
59
0
Order By: Relevance
“…Sometimes they chose to stop using technology, although they needed it, or they had a desire to update their technology use. 57 However, downsizing use of technologies will become a challenge when the health services seek to implement new technologies. Older adults may be reluctant to use new technology that they not yet are familiar with.…”
Section: Discussionmentioning
confidence: 99%
“…Sometimes they chose to stop using technology, although they needed it, or they had a desire to update their technology use. 57 However, downsizing use of technologies will become a challenge when the health services seek to implement new technologies. Older adults may be reluctant to use new technology that they not yet are familiar with.…”
Section: Discussionmentioning
confidence: 99%
“…In line with earlier studies, the results of the study show that implementing technology in everyday lives of older adults or digitalizing care services is not a straightforward procedure. Instead, it is intertwined with the complex social realities of end-users (Stokke et al, 2016;Hedman, Lindqvist, & Nygård, 2016;Bradford et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…As technological development continues to further influence everyday life (Bates & Bitton, 2010;Coughlin, Pope, & Leedle, 2006;Hedman, Lindqvist, & Nygård, 2016), it is important to evaluate the ability to use technology and the effects this human-technology interaction can have on the elderly (Keningsberg et al, 2017). Technologies supporting older adults with and without disabilities have been reported to maintain or improve cognitive functioning, promote feelings of independence and safety, support social connectivity or increase well-being (Coorey, Neubeck, Mulley, & Redfern, 2018;Forsman et al, 2017;Khosravi, Rezvani, & Wiewiora, 2016;McDougall & House, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Technologies supporting older adults with and without disabilities have been reported to maintain or improve cognitive functioning, promote feelings of independence and safety, support social connectivity or increase well-being (Coorey, Neubeck, Mulley, & Redfern, 2018;Forsman et al, 2017;Khosravi, Rezvani, & Wiewiora, 2016;McDougall & House, 2012). In contrast, the involvement of technology in daily activities has been described as potentially demotivating or misleading in the elderly population (Kottorp et al, 2016;Schulz et al, 2015), pointing out that technology can also complicate everyday life. A meta-analysis showed that age is negatively related to perceived ease of technology use (Hauk, H€ uffmeier, & Krumm, 2018) and technologies with greater complexity are more demanding for older compared to younger adults (Ziefle & Bay, 2005), which might indicate a greater challenge for elderly with cognitive impairments.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation